Leveraging Humanized Performance Labeling to Drive Sustainable Building Choices - Azadeh Omidfar Sawyer; Sanaz Saadatifar (Architecture, 2025)
Climate change is a pressing global challenge, significantly influenced by human actions. Considering that buildings account for approximately 40% of total US energy use in the United States, this study examines how humanized energy labeling can influence home buyers’ preferences, shaping total energy demand and usage. “Humanized energy and carbon data” refers to the simplification of complex energy metrics into accessible formats for non-expert audiences. By presenting energy data in a user-friendly manner, this approach aims to empower consumers to prioritize energy-efficient buildings, consequently driving demand for sustainable practices in the building sector. To test this approach, a survey of 163 participants was conducted. Participants were presented with six building façade designs in two rounds: one without energy, carbon, or utility cost data, and the second with comprehensive performance information. Results revealed that 77.3% of participants shifted their preferences after reviewing energy-related data. Furthermore, the study found consistent impacts across demographic groups, highlighting the broad applicability of humanized labeling. These findings confirm the potential of humanized energy labeling to influence housing decisions, driving demand for sustainable practices in real estate. By empowering consumers with accessible information, this approach contributes to mitigating climate change while fostering informed decision-making in the housing market.